Application of Nanocomposit Of Al2O3/Activated Carbon Prepared by Hydrothermal Process for Phenol Removal - Allwar Allwar; Meidita Kemala Sari (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2020)
Nancomposite of Al2O3/activated carbon was prepared from the mixture of alumina oxide (Al2O3) and activated carbon from palm oil shell under the mixture of aquabidest and ethanol (1:1). The mixture was treated by hydrothermal process at 250 oC for 3 h. Resulted Al2O3/ activated carbon was characterized using SEM/EDX for studying the morphology structure of activated carbon and composite showing a like flower structure attached on the surface. The chemical compositions were 73.18%, oxygen 23.72%, aluminium 2.30%, dan silica 2.00%. The efficiency of composite was investigated for removal of phenol in aqueous solution. The maximum adsorption of phenol was obtained at pH 2, adsorbent weight 2 g, contact time 60 min and phenol concentration 100 ppm.